Strategic Human Resources Planning: a Comprehensive Review of the Literature and Analysis of a Framework for Organizational Motivation and Employee Retention - Nugraha, Riad Endra; Rianto, Eko; Supratikta, Hadi (Formosa Journal of Applied Sciences, 2024)
Considered as the first and main practice of human resource management, human resource planning plays a big role. The theoretical basis of the practice of Human Resource planning has been investigated in detail in this article. The author has endeavored to cover and present comprehensive literature on this important practice of Human Resources. The importance of Human Resource planning, its strategic objectives and influencing factors are all covered in this literature study. Also, the study covers the frameworks and models of Human Resource planning and tells the process for retaining and motivating an organization's workforce.